(untitled) (Conferencea, 2022)
This article provides detailed information on the laws, resolutions, decrees of the President of the Republic of Uzbekistan in the field of culture and arts and the lawsmadopted by the Cabinet of Ministers of the Republic of Uzbekistan for this, to improve the legal immunity of each person, the level of legal literacy and their objectives, the basic principles of further development of national culture given.